Поетика драматургії Єлисея Карпенка - Сироватська, М.І. (Харківський національний університет імені В.Н.Каразіна, 2015)
Сироватська М. І. Поетика драматургії Єлисея Карпенка. – На правах рукопису. Дисертація на здобуття наукового ступеня кандидата філологічних наук за спеціальністю 10.01.01 – українська література. – Харківський національний університет імені В. Н. Каразіна Міністерства освіти і науки України, Харків, 2014. У дисертації здійснено цілісний аналіз поетики опублікованих драматичних творів Є. Карпенка 1920-х рр. за допомогою дослідження мотивного комплексу, концепції персонажа й світу, часопросторових координат, образно-символічного наповнення, паратексту, жанрових модифікацій тощо. У заявлених текстах домінантною є модерністська художня парадигма з властивим їй зверненням до універсальних онтологічних категорій, що оприявнюється крізь призму ніцшеанського дискурсу, елементів естетики символізму й експресіонізму. Визначено своєрідність художнього універсуму драматургії митця, що полягає у проблемно-тематичній різновекторності, апеляції до міфопоетики, посиленій умовності основних світомоделюючих координат, символізації часопросторового рівня тощо. Аналіз п’єс Є. Карпенка дає можливість зробити висновок про їхню орієнтацію на «новодраматичний» тип конфлікту «людина–Стіна», що на поетикальному рівні виявляється через послаблення драматургічної динаміки, особливе навантаження вербальної площини, трансформацію ремарок у ритмотвірний та сугестуючий засіб, тенденції до міжродових і міжжанрових взаємовпливів.
The poetics of Yelisey Karpenko’s drama
Syrovatska M. I. The poetics of Yelisey Karpenko’s drama. – The manuscript rights. The thesis for the degree of Candidate of Philological Studies, speciality 10.01.01 – Ukrainian literature. – V. N. Karazin Kharkiv National University, Ministry of Education and Science of Ukraine, Kharkiv, 2014. In the thesis the poetics of Ye. Karpenko’s published drama of the 1920-s is analysed by means of studying the motif complex, a person and the world conception, time and space coordinates, figurative and symbolic filling, paratext, genre modifications, etc. It is established that in the author’s plays (“Edelweiss”, “White Nights”, “Soil”, “In the Valley of Tears”, “Momot Nir”, “At Holy Night”, “At Autumn night”) dominant is modernist artistic paradigm that has a peculiar appeal to universal ontological categories that show themselves through the prism of Nietzschean ideas, elements of symbolism and expressionism aesthetics. The conception of personality that is in the conflict relationships with the entity is also defined and is represented by diverse gallery of characters of a human being-“alive symbol” and -marionette. The art conflict of corporeal and spiritual as well as the motive of ontological waiting is conceptual and runs through the whole drama of the writer. The analysis of Ye. Karpenko’s plays gave an opportunity to make a conclusion about their orientation to the “new drama” type of the conflict “a person–a wall”, which on the poetical level manifests itself through drama dynamic’s relaxation, special strain of verbal level, remarks’ transformation into rhyme- and suggestive-making way, tendencies of intergeneric and intergenre interference, sketchiness, etc. The existential level of the problems is dominant; it is represented by motives of love, ownership (filling), illness, brutality, keeping silence, orphanhood, world’s absurdity, person’s alienation, longliness, grief, predestination in post-revolution reality, death inevitability, etc. The originality of art universe of artist’s drama that is in the problem- thematic of multidirectionality, an appeal for myth-poetical level, intensified conventionality of the main world-modelling coordinates, special symbolization of time-space level and others is defined. The dominating idea of temporal model of the title (“White Nights”, “At Autumn night”, “At Holy Night”) that is author-textual and genre-making (“festal” drama) is stressed. The idea of disharmony of the reality, which is realized on the different poetical levels: character’s (dramatis personae have obvious physical or psychological deficiency); literary speech (quite often they name their own pathological state) and symbolical (the system of images-symbols gives an opportunity to create the integral notion of the state of general morbidity of the environment), is fundamental for Ye. Karpenko’s art world of drama. The interpretation of the model of the chronotope of the artist’s drama allows to state running through appeal to mythopoetics, which is symbolic for modernistic conception of action. It is established that four nature elements (earth, water, fire and air (wind)) make a concentrated model of the art universe of playwright’s dramas. It is characteristic that such appeal to the elements in Ye. Karpenko’s works is always connected with the idea of verticality as spiritual superiority (a mountain/earth being associated with the “top” is traditionally opposite to water/abyss that is associated with the “bottom”). It is proved that material fullness of literary style of author’s drama works is practically main condition of text’s integral perception and plays extremely important sense-forming part, as it is the sphere of representation of characters’ activity, as well as reflects their internal world, shows existential state of nervousness, alarm, dependence, obsession, intuitive-spiritual sphere of person’s entity. The central space image of the art universe of the plays is locus of house (as a Swiss house, a hut, a palace, a lodging, a wall of the house, etc) that in the majority of the artist’s works in spite of traditional semantics of stability, reliability and protection signs sickliness, betrayal, forlornness, independence and death. It’s defined that due to unreal, temporal and locative categories the author managed to show the unique essence of a person in the attempt of finding himself/herself in the condition of abnormal reality in an integral and fundamental way. The analysis proved the presence in the artist’s drama of the great number of intertextual parallels: an appeal to Ancient Greek mythology, bible allusions, cites of T. Shevchenko’s, O. Oles’, M. Voronyi’s works, knowledge of the history of the world national liberation movement, etc. It was as well discovered that intermedialety as author’s strategy appears as sense-forming characteristics and gives metatext characteristics to symbolist plays of the author. Among its methods in the drama sense-forming part of musical source, sound-description, rhythm-intonation organisation of the texts, emphasising of the colour model, using of choreographical elements and others should be named. The author’s works is represented in a wide Ukrainian and world literary and art context that allows to make conclusions about the place and the part of Ye. Karpenko’s drama of the 1920-s as a “transitive” phenomenon in the literature of the modernism age. Through the mediation of intertextual and authotextual types of analysis the aesthetic heterogeneity of Ye. Karpenko’s drama is established. Plays “Soil” and “In the Valley of Tears” stand out due to their original interpretation of the precedented motive of infanticide in the spirit of expressionism aesthetics. The symbolist model of the world that is realized in the drama poem “White Nights” and drama “Edelweiss” through powerful myth-poetical aspect is unique. Running through in their symbolism one-act plays “At Holy Night” and “At Autumn night” represents the peculiarity of action-free symbolist theatre of M. Maeterlinck. Taking into account the originality of plays of the author the prospectivity of further workshops on the artist’s plays in general and some of its aspects in particular (as for example, myth-poetical paradigms, Bible code, intermedial component, etc) should be named as perspective.
Keywords: поетика; модернізм; символізм; експресіонізм; міфопоетика; «нова драма»; конфлікт; драматургічна ремарка